Factors predicting perceptions of meat and dairy foods among college students at a land-grant institution: an observational, analytical study - Carlson, Brynn Mandell (Kansas State University, 2021)
Meat and dairy consumption are staples of the typical American diet, yet interest in plant-based dietary patterns has been increasing in recent years. Perceptions of red meat, dairy products, and their plant-based alternatives are relatively unknown in college-aged students, who are unique in the sense that many are likely making their own food intake decisions for the first time. The purpose of this observational, analytical study was to determine the predictive value of student characteristics for attitudes regarding red meat and dairy consumption as well as plant-based alternatives to these types of foods. A modified version of a previously validated 25-item survey that included 12 items related to perceptions of red meat consumption, 11 items related to perceptions of dairy consumption, and two items related to perceptions of plant-based alternatives to red meat and dairy consumption was distributed to students attending Kansas State University. A stratified random sample was determined, resulting in 5,300 surveys being distributed and 528 being fully completed, for a 10% completion rate overall. Demographic information, including age, gender, race/ethnicity, college affiliation, reported dietary pattern, educational attainment, self-reported level of agricultural knowledge and the size of the population in which the students were primarily raised was also collected. Preliminary data analyses indicated that a majority of survey participants were female (67.2%), ages 18–25 (89%), white (86.8%), fell into the late undergraduate academic level (juniors and seniors, 53.2%), and consumed an omnivorous dietary pattern (91.7%), with a somewhat even distribution of participants falling into each population size and self-reported level of agricultural knowledge category. Survey respondents were representative of the larger university population as well as all individual colleges (excluding the College of Veterinary Medicine which was not represented). Data dimensionality reduction procedures included a principal component analysis that revealed five unique factors and included a subsequent factor analysis that confirmed the five factors. A series of linear regressions was then performed to determine the predictor variables that explained the variability in perceptions of red meat and dairy intake, as well as plant-based alternatives. The five factors revealed through the principal component analysis were positive perceptions of red meat (factor 1), negative perceptions of red meat (factor 2), negative perceptions of toxins, hormones, and antibiotics in red meat (factor 3), negative perceptions of dairy products (factor 4), and positive perceptions of dairy products (factor 5). The consistent significant predictors of agreement with attitudes toward red meat and dairy consumption across all five factors were college affiliation and dietary pattern. Participants identifying as students in the College of Agriculture and participants consuming an omnivorous diet indicated significantly stronger agreement with more positive perceptions of red meat and dairy across all five factors compared to all other college affiliations and reported dietary patterns, respectively. Additionally, race/ethnicity was a significant predictor for factors 1 and 2, self-reported level of agricultural knowledge was a significant predictor for factors 1 and 3, and the size of the population in which the students were primarily raised was a significant predictor in the model for factors 2, 3, and 4. Kansas State University is a land grant, agriculturally oriented university with a relatively homogenous student population, and high levels of participation in diets that include animal products. Therefore, despite recent trends of increasing interest in and consumption of plant-based dietary patterns, students at Kansas State University tend to maintain positive perceptions of red meat and dairy. In the future, the results of this study can be used to tailor education regarding red meat, dairy, and plant-based alternatives to students with differing educational backgrounds and dietary patterns, develop a more thorough measurement of perceptions of plant-based dietary patterns, and inform research that determines additional predictors that may be associated with college-aged students’ perceptions of red meat, dairy, and plant-based alternatives.
Keywords: Meat; Dairy; Perceptions; Agriculture; Dietary pattern; Principal component analysis